2021
DOI: 10.1007/s11548-020-02299-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of AI quantified COVID-19 chest CT and patient outcome

Abstract: Purpose Severity scoring is a key step in managing patients with COVID-19 pneumonia. However, manual quantitative analysis by radiologists is a time-consuming task, while qualitative evaluation may be fast but highly subjective. This study aims to develop artificial intelligence (AI)-based methods to quantify disease severity and predict COVID-19 patient outcome. Methods We develop an AI-based framework that employs deep neural networks to efficiently segment lung lobes and pulmonary opacities. The volume rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…A total of 2/24 studies used CT imaging features (Ning et al, 2020; X. Fang et al, 2021). Particularly, Ning et al used CT images in addition to clinical features, while Fang et al developed an artificial intelligence (AI) framework using deep neural networks to segment lung lobes and pulmonary opacities, and baseline ML methods to predict mortality based on radiological severity scores (accounting for the volume ratio of pulmonary opacities in each lung lobe).…”
Section: Class Of Featuresmentioning
confidence: 99%
“…A total of 2/24 studies used CT imaging features (Ning et al, 2020; X. Fang et al, 2021). Particularly, Ning et al used CT images in addition to clinical features, while Fang et al developed an artificial intelligence (AI) framework using deep neural networks to segment lung lobes and pulmonary opacities, and baseline ML methods to predict mortality based on radiological severity scores (accounting for the volume ratio of pulmonary opacities in each lung lobe).…”
Section: Class Of Featuresmentioning
confidence: 99%
“…However, CT images are usually visually interpreted by radiologists with diverse levels of experience, which is subjective with large variability that is unable to quantitatively assess the disease severity and is also time-consuming and laborintensive. Previous studies have shown that quantitative CT is comparable or superior to visual CT score in assessment of the severity of COVID-19 (28,45,46). Recently, several studies have used quantitative CT to predict clinical outcomes via AI software in patients with COVID-19 (43,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of clinical characteristics and radiomic features from CT could achieve better accuracy in prediction (18,19). Some studies also apply deep learning to automatically learn features from CT images or in combination with clinical data and radiomics for risk assessment of COVID-19 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Deep learning and radiomics can be a more objective, quantitative, and stable system for the assessment of the COVID-19 disease course.…”
Section: Introductionmentioning
confidence: 99%
“…Severity assessment facilitates monitoring the COVID-19 infection course. Furthermore, it is closely related to prognosis outcomes ( Fang et al, 2021 ), and detection of high-risk patients with early intervention is highly important to lower the fatality rate of COVID-19. Thus, we reviewed AI algorithms and models proposed for COVID-19 severity assessment and prognosis prediction in one section.…”
Section: Covid-19 Severity Assessment and Prognosis Predictionmentioning
confidence: 99%